EFFECTIVENESS OF LAVENDER AROMATHERAPY AND CLASSICAL MUSIC THERAPY IN LOWERING BLOOD PRESSURE IN PREGNANT WOMEN WITH HYPERTENSION - Sri Maisi; Suryono Suryono; Melyana Nurul Widyawati; Ari Suwondo; Suryati Kusworowulan (Belitung Nursing Journal, 2017)
Background: Hypertension during pregnancy remains high in Indonesia. It is a major cause of maternal death. Aromatherapy lavender and classical music therapy are considered effective in lowering blood pressure in hypertension. Objective: To examine the effect of lavender aromatherapy and classical music therapy in lowering blood pressure in pregnant women with hypertension. Methods: A quasi-experimental study with pretest-posttest control group design. There were 52 pregnant women selected using simple random sampling, divided into lavender aromatherapy group, classical music group, combination of aromatherapy and music group, and control group. Sphygmomanometer was used to measure blood pressure. Mann Whitney and Post Hoc test were used for data analysis. Results: Results showed that four groups had a significant decrease in systolic blood pressure after given intervention with p-value <0.05. The mean decrease of systolic blood pressure among four groups was: lavender group (5.77 mmHg), music group (7.23 mmHg), combination group (9.54 mmHg), and control group (3.67 mmHg); and the mean decrease of diastolic blood pressure was: the lavender group (2.77 mmHg), music group (0.61 mmHg), combination group (8.23 mmHg), and control group (3.42 mmHg). Conclusion: There was a significant effect of lavender aromatherapy and classical music therapy in lowering blood pressure in pregnant women with hypertension. However, the combination of both interventions was more effective than lavender aromatherapy or music therapy alone.